How Many Types of Ideas Must be Considered to Reconstruct the Real Concept of Ideas in Kant? - Lewin, Michael (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Kraus’s ‘Kant’s Ideas of Reason’ offers a ‘perspectivalist interpretation’ of a part of the Transcendental Dialectic. I will focus on two central topics: the concept of ideas and the concept of reason. First, I argue that Kraus’s reconstruction of the concept of ideas requires significant refinement. Despite what the title of her work might suggest, her analysis is limited to transcendental ideas without engaging with Kant’s broader typology, which includes at least seven distinct types of ideas. Greater attention to the fundamental features of the concept of ideas, as well as to the relevant scholarship, could help avoid the introduction of the problematic ‘isms’ ‘noumenalism’ and ‘fictionalism’. Second, I highlight that Kraus does not clearly distinguish between reason in its broader and narrower senses, nor does she provide a precise definition of reason in the narrower sense. I propose modifying the ‘perspectivalist interpretation’ in accordance with my suggestions.